Simulasi Perangkat Lunak Alat Pengeruk Sampah Otomatis Menggunakan Logika Fuzzy Mamdani - Saputra, Gusti (Universitas Trilogi, 2018)
The garbage crusher is one of the tools that is considered to have a high level of effectiveness in overcoming the problem of garbage in the river around DKI Jakarta. However, the dredging tool that is currently available is still moving manually in operation, which results in scheduling human resources that are less than optimal in every operation. This requires a garbage dredger whose operation can work automatically so that the scheduling of human resources in the operation of the garbage crusher is optimal. In this research, automatic garbage scrapers will be simulated using a Fuzzy Inference System. Simulation in the form of knowledge making on decisions that will later be on automatic garbage scrapers using a fuzzy inference system.